Synthesizing The Domain Of Lean Practices In Manufacturing Operations : A Review - Yusup, Muhamad Zaki; Wan Mahmood, Wan Hasrulnizzam; Salleh, Mohd Rizal; Muhamad, Mohd Razali; Saptari, Adi (Penerbit UTM Press, 2015)
-